The Message of Tauhid in Seserahan: Reinterpreting Premarriage Traditions Through the Lens of Maqashid Syariah - Mursyid Fikri; Abur Hamdi Usman; Rudianto; Muhammad Syahruddin; Akram Ista (LP2M IAIN Palopo, 2026)
The tradition of seserahan in Indonesian Muslim society constitutes an important part of the premarital process and carries symbolic, moral, and spiritual meanings. However, in contemporary practice, seserahan is often reduced to a display of prestige, consumption, and social status, thereby obscuring its religious substance. This study aims to reinterpret the tradition of seserahan through the perspective of tauhid and maqāṣid al-syarī‘ah, and to examine the extent to which this tradition remains aligned with the principle of maslahah in Muslim family life. This research employs a qualitative systematic literature review of 20 scholarly publications published between 2021 and 2025, selected from relevant academic sources on marriage, premarital traditions, Islamic law, and maqāṣid al-syarī‘ah. The data were analyzed thematically using two analytical parameters, namely tauhid as a spiritual-theological framework and the five essential objectives of maqāṣid al-syarī‘ah: hifzh ad-dīn, hifzh an-nafs, hifzh al-‘aql, hifzh an-nasl, and hifzh al-māl. The findings show that seserahan can reflect Islamic values and contribute to the realization of the objectives of sharia when it is practiced proportionally, ethically, and with a worship-oriented intention. At the same time, the literature also indicates a shift in meaning in modern society, where seserahan is frequently shaped by materialism and social pressure. This study concludes that reconstructing seserahan on the basis of tauhid and maqāṣid al-syarī‘ah is necessary in order to restore its function as a medium of moral education, spiritual commitment, and the formation of a sakinah family.